Management and Ensuring the Quality in the Educational Organizations (Standards, Models and Methods) in the light of Saudi Arabia’s Vision 2030 - Al-Fahmi, Marzouq Matar (Journal of Educational and Psychological Sciences, 2020)
The study aimed to investigate standards, models and methods of management and ensuring the quality in the educational organizations through reviewing the variable intellectual visions that dealt with quality standards and models, and manner of its management and fields of its application in the educational organizations in the light of Saudi Arabia’s Vision 2030. The study used the historical method, and the study tool was represented in revising the previous studies and researches that was written in management and ensuring the quality in the educational organizations. Main findings: 1- The quality of education represents a comprehensive strategy for development of the educational organizations. 2- The education system is mainly concerned on application of quality department to many parameters, of which mainly: International competition, increased rates of joining and spending on education, emerging of new techniques in information systems and methods of production, and taking into consideration the educational services through satisfaction of users or customers. 3- The main standards of quality of education are represented in fulfilling the needs of the users, the needs of the planners and financiers of the educational system, efficiency of educational leadership, professional development of the educational and departmental systems, and development of performance and quality of outputs. 4- There are many mechanisms that can be applied for management of quality of education, of which mainly: self-evaluation, external evaluation, and evaluation of outputs. 5- The quality fields and its management widen due to variability of elements and components of the educational system, although it’s concerned in 3 main fields, which are: emphasis on needs of the users, efficiency of the educational organization, and effectiveness of the educational leadership. Based on the results of the study, some suggestions and recommendations were represented for management and ensuring the quality in the educational organizations.